Diversity, Equity and Inclusion for Business & Management - Everett, Sally; Hill, Ian (SAGE Publications, Ltd. (UK), 2025)
Diversity, Equity and Inclusion for Business & Management is a comprehensive and accessible guide to the evolving landscape of DEI in the discipline. Developed in collaboration with the Chartered Association of Business Schools and written by experts in their fields, this book offers a unique approach, with discipline-focussed chapters that cover Strategy, Leadership, Organisational Behaviour, Marketing, Accounting, Finance and more. As you read about how issues of social justice, diversity, and inclusion relate to your studies and future careers, you will be supported by a range of learning features, including global case studies, critical reflections, and practice questions. This book is essential reading for students of business and management taking modules in DEI and diversity management, as well as those who are interested in responsible business practice. Sally Everett is Professor of Business Education and Vice Dean (Education) at King’s Business School, King’s College London Ian Hill is a Lecturer in Work and Organisations (Education) at King’s Business School, King’s College London